1-Anilino-5-methyl-1H-1,2,3-triazole-4-carbaldehyde - Cunha, Anna C.; Jordão, Alessandro K.; Souza, Maria C. B. V. de; Ferreira, Vitor F.; Almeida, Maria C. B. de; Wardell, James L.; Tiekink, Edward R. T. * (International Union of Crystallography, 2016)
The title compound, C10H10N4O, is twisted about the Nring-Namine bond with the dihedral angle between the 1,2,3-triazolyl and N-bound phenyl rings being 79.14 (9)°. The C-bound aldehyde group is coplanar with the triazolyl ring, with the N-C-C-O torsion angle being 3.5 (3)°. While coplanar, the aldehyde O atom is orientated in the opposite direction to the triazolyl-bound methyl group. The most prominent feature of the molecular packing is the formation of zigzag chains (glide symmetry) along the b axis and mediated by amine-N-H...N(triazolyl) hydrogen bonds. The chains are connected into supramolecular layers by phenyl- and methyl-C-H...O(aldehyde) interactions, with phenyl groups projecting to either side. Layers stack along the c axis with no directional interactions between them.